Indonesia’s pro-people foreign policy: the protection of Indonesian women migrant workers in Malaysia in 2022 - Arie Kusuma Paksi; Pebria Prakarsa Renta (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
This study investigates the Indonesian government's strategies to safeguard its informal sector in Malaysia, which has experienced considerable human rights violations and exploitation. Such incidents breach both the Memorandum of Understanding (MoU) and Law No. 18 of 2017 on the Indonesian migrant workers' protection. Utilizing the pro-people foreign policy theory and the citizen protection concept, this research explores the government's responses to these issues as a protective measure for its citizens. Employing a qualitative descriptive method, data was gathered through library studies. The findings reveal that the Indonesian government, in its bid to protect indonesian women migrant workers in malaysia by 2022, has publicly criticized the Malaysian government, implemented a Moratorium, and pushed for immediate bilateral meetings between the two nations. Hence, the study concludes that these efforts have positively influenced the protection of indonesian women migrant workers in malaysia in 2022